Quality controls of radiolabeled compounds 131I–Hippuran as PSTNT-BATAN product using electrophoresis method. (January 2020) - Mulyati, T S; Rosyidiah, E; Suherman, A; Iswahyudi, I; Wibawa, T H A
Abstract: The labeled compound 131 I-Hippuran has been known for a long time and was still being used by some hospitals as a medical kit for the study of dynamics kidney function. The application of Labelled compound 131 I-Hippuran begins by intravenous injection to the patients, then monitor the process of biodistribution, secretion, and excretion of Labelled compound 131 I-Hippuran using Renographs. The Bandung TRIGA 2000 reactor has obtained an operating license from BAPETEN in 2017, and has been operating at 800 kW to irradiate various elements including Tellurium to produce radioisotope Iodine-131. Iodine-131 was used as a radioisotope material in Labelled compound 131 I-Hippuran, which was produced to fulfill the requests from An-Nur Hospital, Yogyakarta. Labeled compound 131 I-Hippuran used in hospitals must meet the requirements of Indonesian Pharmacopeia, one of the parameters tested is radiochemical purity. The method used to determine the radiochemical purity is the paper electrophoresis method with phosphate buffer electrolyte pH 9, at a voltage of 300 volts for 1 hour. The radiochemical purity of 131 I-Hippuran using the column chromatography method obtained yield more than 70% with radiochemical purity of 98.81 ± 1.06%. Based on these data, the radiochemical purity of the 131 I-Hippuran kit has met the requirements set by Pharmacopoeia Indonesia V that is >90%.